Design of an adapted standing frame for rehabilitation of children with mental deficiency - Machado, José Mendes (2011)
A standing frame is a mechanical (old) or mechatronic (new) equipment, that has as main goal to correct the incapacity of certain individuals for assuming the body’s vertical position. The existing standing frames, on the market, do not allow easy placement of the patient on the device, do not allow full mobility (within and outside of buildings), they are not versatile, they are not modular and they do not allow children to have occupational activities during treatments. This paper presents the project of a Standing frame for use in the treatment of children with mental deficiency. The Standing frame presented in this paper takes into account the limitations mentioned above and is perfectly adapted to this very specific and very special target people. The main features of the equipment whose project is presented in this article are the modularity, easiness of placing the patient and easiness of use, especially when the patient, and family, need to travel and need to carry with them the standing frame.